Improving the Quality of Health Management Information System: Determinants of Effective Data Management among Data Management Officers in a South West State in Nigeria - Yetunde W. Olagbuji; Adewale M. Adejugbagbe (Archives of Current Research International, 2018)
Producing quality data and adequate information is crucial for decision making at all levels of the health system. Effective data management among health workers is seen as a promising choice for improving quality of data and continue professional development in health care. This study determined the prevalence of good data management practice and identified it’s determinants among health workers in Ondo State, Nigeria. A descriptive cross-sectional study was conducted among 532 data management officers in the Primary Health Care Centers (PHCCs) in the community and Local Government Area (LGA) headquarters in the State. Data analysis suggests that the prevalence of good data management is very low (9.7%), particularly among data officers in the community PHCCs, with the low level of education and without information and Communication Technology (ICT) equipment. Our result calls for the introduction of basic computer application courses in the medical curriculum of health training institutions engaged in the professional development of health workers. Also, essential ICT equipment for data processing and management should be made available in all the PHCCs for effective data management.